Green-synthesized silver nanoparticles from edible plant extracts ameliorate cadmium chloride-induced hepatorenal and testicular toxicity in rats - Abu-Okail, Akram; Aljohani, Abdullah S. M.; Mousa, Ayman M.; El-Nashar, Heba A. S.; El-Shazly, Mohamed; Sayed, Ramy K. A.; Al Abdulmonem, Waleed; Farghali, Mohamed; Kamaly, Heba F.; El-Ashmawy, Ibrahim M.; Abdellatif, Ahmed A. H.; Hamad, Nashwa (Frontiers in Cell and Developmental Biology, 2025)
BackgroundCadmium (Cd) is widely known as an environmental toxicant, ranked as the seventh most toxic heavy metal. Exposure to cadmium through inhalation and ingestion can lead to serious health issues, including liver damage, kidney degeneration, testicular problems, and blood disorders in both humans and animals.ObjectiveThis study aimed to evaluate the protective effects of biosynthesized silver nanoparticles (AgNPs) against cadmium chloride-induced hepatic, renal, and reproductive toxicity in male rats.MethodsAgNPs were synthesized via chemical reduction in silver nitrate using a combination of three plant extracts, namely, Petroselinum crispum, Zea mays silk, and Acacia senegal. The obtained AgNPs were characterized and subjected to an in vivo study. Forty healthy adult male albino rats (200–230 g) were divided into four groups (n = 10): G1: negative control, G2: rats received AgNPs (200 mg/kg b.w), G3: rats received cadmium chloride (5 mg/kg b.w), and G4: rats received AgNPs (200 mg/kg b.w.) followed by cadmium chloride (5 mg/kg b.w) after 90 min. All treatments were administered daily for 35 days. Biochemical assessments included liver enzymes (alanine transaminase, aspartate aminotransferase, and alkaline phosphatase), kidney markers (urea and creatinine), testicular hormones (testosterone, luteinizing hormone, and follicle-stimulating hormone), lipid profile (low-density lipoprotein, high-density lipoprotein, and triglyceride), and antioxidant markers (total antioxidants and malondialdehyde). Histopathological studies were performed on the liver, kidney, and testicular tissues.ResultsSynthesized AgNPs exhibited spherical morphology, with an average nanosize distribution of 5.28–21.47 nm. Cadmium chloride exposure significantly elevated liver enzymes, lipid markers, urea, creatinine, and MDA while decreasing testicular hormone levels (testosterone and luteinizing hormone), indicating hepato-renal and testicular damage, alongside histopathological damage in all examined organs. Co-administration of AgNPs markedly ameliorated these biochemical alterations, improving liver and kidney function, restoring total antioxidant capacity, and normalizing lipid, protein, and testicular hormone profiles. Histopathological results revealed that treatment with AgNPs restored the angiopathic, degenerative, and necrotic changes prompted by cadmium chloride administration.ConclusionAgNPs biosynthesized from combined extracts of P. crispum, Z. mays silk, and A. senegal demonstrated significant protective effects against cadmium chloride-induced toxicity. Their antioxidant and free radical scavenging properties suggest potential therapeutic value in mitigating environmental cadmium toxicity.